ANALISIS KESULITAN BELAJAR MATEMATIKA DISKRIT PADA MAHASISWA MANAJEMEN INFORMATIKA AMIK BINA SRIWJAYA PALEMBANG - Lidya Cahyani (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
This research is a descriptive analysis research, that aims to describe the difficulties faced by students while studying discrete mathematics and the factors that cause difficulties themselves. It’s needs to be studied in depth so that discrete mathematics learning for the new semester, the difficulties experienced by students can be minimized by the new teaching method by paying attention to class conditions during learning. The subjects of this study were informatics management students in 2nd semester, AMIK Bina Sriwijaya Palembang which numbered 28 people. Data on the difficulties of students are collected by test, documentation, and observation methods. Data that has been collected is then analyzed to find out the discrete mathematical learning difficulties and their causes. Based on data obtained from student grades during discrete mathematics learning, the average score is only around 45.66. The value category is in a low range, which is less.